A 9600‐year record of water table depth, vegetation and fire inferred from a raised peat bog, Prince Edward Island, Canadian Maritimes. (14th July 2016) - Peros, Matthew; Chan, Kathleen; Magnan, Gabriel; Ponsford, Leila; Carroll, James; McCloskey, Terry
ABSTRACT: A 582‐cm‐long peat core was collected from Baltic Bog, an ombrotrophic peatland in north‐eastern Prince Edward Island, Canada. The core was studied for testate amoebae, plant macrofossils, macrocharcoal, peat humification and organic matter content. The results show that Baltic Bog first developed ∼9600 cal a BP as a minerotrophic peatland (fen) dominated by Cyperaceae. At 8200 cal a BP, the fen transitioned into a peat bog dominated by Sphagnum . Between 8200 and 4000 cal a BP, water table depth (WTD) was generally low and the bog surface supported trees such as Picea mariana . From 4000 to 1700 cal a BP, WTD rose and the bog became more open. The macrocharcoal results show that the period ∼2000–1000 cal a BP was characterized by several fire events that may have occurred on the bog surface at the core site. The results presented in this paper correspond closely with previous fossil pollen research done at Baltic Bog and suggest that regional climate change was a key factor in controlling long‐term WTD variability and vegetation change at the site.